Oxypoda convergens Casey 1893 - Klimaszewski, Jan; Godin, Benoit; Davies, Anthony; Bourdon, Caroline; Horwood, Denise (Zenodo, 2018)
Oxypoda convergens Casey Distribution Origin Nearctic Distribution Canada : AB, LB, MB, NB, NF, NS, ON, QC. USA : IA, MO, NY New provincial Canada: Manitoba: Moose Lake, 2016-IX-19, 49.2018°N, 95.3423°W, 353 m, record mushroom, sifting, B. Godin & D. Horwood (BGC) 1 female. References Casey 1893, Klimaszewski et al. 2011, 2018 Collection and habitat data. Habitat (outside of the study area). In various forest types including white spruce, mature black spruce, red spruce, mature 50-year-old balsam fir, oak, maple, yellow birch/ balsam fir white pine forests, red oak forests, mixed forests, and old eastern white cedar forest; often very common in decaying gilled mushrooms in the above forest habitats, especially those dominated hardwoods. Also in riparian habitats, and a meadow with Salix shrubs. Several collected from decaying corncobs and cornhusks. Collecting period . V–XI (most common in August and September). Collecting method . Unbaited and carrion-baited pitfall traps, processing forest litter through Berlese funnels, Luminoc pitfall-light traps, Lindgren traps, intercept traps, and treading leaf litter at the edge of a pond, sifting decaying mushrooms. : Published as part of Klimaszewski, Jan, Godin, Benoit, Davies, Anthony, Bourdon, Caroline & Horwood, Denise, 2018, Forty new records of aleocharine beetles, and two new species in the genera Acrotona Thomson and Atheta Thomson, for the province of Manitoba, Canada (Coleoptera: Staphylinidae: Aleocharinae), pp. 1-33 in Insecta Mundi 2018 (641) on page 26, DOI: 10.5281/zenodo.5173990 : {"references": ["Casey, T. L. 1893. Coleopterological notices. V. Annals of the New York Academy of Sciences 7 (6 - 12): 281 - 606, pl. 1 [Separate publ. in 1893].", "Klimaszewski, J., D. Langor, G. Pelletier, C. Bourdon, and L. Perdereau. 2011. Aleocharine beetles (Coleoptera, Staphylinidae) of the province of Newfoundland and Labrador, Canada. Pensoft Publishers (Series Faunistica No. 98); Sofia-Moscow. 313 p.", "Klimaszewski, J., R. P. Webster, D. W. Langor, A. Brunke, A. Davies, A. F. Newton, C. Bourdon, M. Labrecque, J. A. Dorval, and J. H. Frank. (2018). Aleocharine rove beetles of eastern Canada (Coleoptera, Staphylinidae, Aleocharinae): a glimpse of megadiversity. Springer International Publishing AG; New York. 879 p."]}